Developing taxonomy for the domain ontology of construction contractual semantics: A case study on the AIA A201 document. Issue 3 (August 2015) - Niu, Jia; Issa, Raja R.A.
Highlights An ontological model is developed from definitions found in a contract. A synthesized methodology for taxonomies for contractual semantics is established. The taxonomy is validated using a case study for a standard construction contract. Developed enhanced ontology-based application for sharing contract domain knowledge.